In vitro sliding‐driven morphological changes in representative esthetic NiTi archwire surfaces. Issue 10 (17th August 2015) - Choi, Samjin; Park, Dong‐Jin; Kim, Kyung‐A; Park, Ki‐Ho; Park, Hun‐Kuk; Park, Young‐Guk
ABSTRACT Objectives This study investigated the effects of sliding on the ultrastructure of three representative esthetic superelastic 0.014 inch nickel‐titanium (NiTi) archwires. Methods: Atomic force microscopy, scanning electron microscopy, and light microscopy were used to estimate the surface roughness of archwires and bracket systems. Energy‐dispersive X‐ray spectroscopy was used to estimate the molecular differences between coated and uncoated areas. A combination of four different types of 0.014 inch metallic wires and two different types of 0.022 inch × 0.028 inch conventional brackets were evaluated by in vitro sliding tests using a novel self‐made tensile‐strength tester with a miniature load cell and syringe pump. The NiTi wires included an uncoated NiTi archwire (CO group), epoxy resin‐coated NiTi archwire (ER group), Teflon®‐coated NiTi archwire (TF group), and Ag/biopolymer‐coated NiTi archwire (AG group). The brackets included contained stainless steel (SS) and ceramic (CE) brackets. Results: Both ER and TF wire groups exhibited less surface roughness than CO wire groups. The AG group showed the highest surface roughness compared with the others because of its silver particles (P<0.001, ANOVA test). In vitro sliding tests led to a significant increase (P < 0.001, ANOVA test) in the surface roughness of all 0.014 inch NiTi wires regardless of bracket type. The wire groups combined with SS brackets were rougher than those of CE brackets regardless of the coating materials because of exfoliation of the coating materials. The TF‐SS group showed the highest increase (fivefold) in surface roughness compared to the others, while the ER groups showed the lowest increase (1.4‐fold) in surface roughness compared with the others (P < 0.001, ANOVA test). Conclusions: The results suggested that the sliding‐driven surface roughness of superelastic NiTi archwires is directly affected by coating materials. Although the efficiency of orthodontic treatment was affected by various factors, epoxy resin‐coated archwires were best for both esthetics and tooth movement when only considering surface roughness. Microsc. Res. Tech. 78:926–934, 2015. © 2015 Wiley Periodicals, Inc.